1998
DOI: 10.1143/jjap.37.l325
|View full text |Cite
|
Sign up to set email alerts
|

The Chaotic Oscillation of the Single-Mode He-Ne(6328 Å) Class A Laser

Abstract: The confirmation of chaotic oscillation in a single-mode He-Ne(6328Å) standing-wave class A laser, by means of delayed feedback with an external mirror is reported. Varying the reflectivity of the external mirror, the time series of the laser output power are observed. By constructing the phase portraits and estimating Lyapunov exponents, the transition from a point attractor to a strange attractor is confirmed by the positive Lyapunov exponents in the chaotic region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
1
14
0
3
Order By: Relevance
“…Recently, similar studies have successfully demonstrated experimentally the occurrence of LFFs in a class-A He -Ne laser. 3,4 These results were confirmed by numerical simulations of the class-A laser equations. 5 However, few lasers can be described by a field equation only.…”
supporting
confidence: 53%
“…Recently, similar studies have successfully demonstrated experimentally the occurrence of LFFs in a class-A He -Ne laser. 3,4 These results were confirmed by numerical simulations of the class-A laser equations. 5 However, few lasers can be described by a field equation only.…”
supporting
confidence: 53%
“…In our second paper, 17) chaotic oscillation from a class A laser is first demonstrated in a single-mode He-Ne (6328 Å) standing-wave laser which has an external mirror without the PZT. The threshold value of a control parameter for the chaos is approximately 16% of the external mirror reflectivity (power).…”
Section: Experiments Imentioning
confidence: 99%
“…In §2, we summarize the results of experiments I, 17) in which chaotic oscillation in a class A He-Ne (6328 Å) single-mode laser was observed by means of delayed feedback by tilting the external mirror. Section 3 is devoted to improved experiments (experiments II), in which we use a ND filter instead of tilting the external mirror; we also study the effect of the pumping parameter on the chaotic behavior of a class A laser.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this also affects the introduction of optical chaos in the devices, since a nonlinear system exhibiting deterministic chaos must be described by at least three dynamical variables; 5 therefore, in a class B laser, the imposition of only one external variable is required, whereas two are needed to observe the same effect in a class A device. 6 We present here the results of time-resolved studies of the stimulated emission photocurrent, which were carried out using the Dutch free-electron laser FELIX. These show g ϳ 50 ps and indicate that class B dynamics should be expected from these structures.…”
Section: Introductionmentioning
confidence: 99%